X-ray two-photon absorption with high fluence XFEL pulses. (August 2015) - Hoszowska, J; Szlachetko, J; Dousse, J-Cl; Błachucki, W; Kayser, Y; Milne, Ch; Pajek, M; Boutet, S; Messerschmidt, M; Williams, G; Chantler, C T
Synopsis: We report on nonlinear interaction of solid Fe with intense femtosecond hard x-ray free-electron laser (XFEL) pulses. The experiment was performed at the CXI end-station of the Linac Coherent Light Source (LCLS) by means of high- resolution x-ray emission spectroscopy. The focused x-ray beam provided extreme fluence of ∼10 5 photons/Å 2 . Two-photon absorption leading to K-shell hollow atom formation and to single K-shell ionization of solid Fe was investigated.